Likely effects of a trade war for US agriculture? Sad! - Glauber, Joseph W. (Guelph University, 2017)
US farmers and ranchers overwhelmingly supported Donald Trump in the recent Presidential election citing their concerns with overly burdensome regulations and their belief that the President-elect was the best candidate to lead the country over the next four years. Yet, that support came despite promises made by President-elect Trump during the campaign to levy taxes against China exports to the United States, to renegotiate NAFTA, to withdraw from the Transpacific Partnership (TPP) agreement, and to pull the US out of the World Trade Organization if membership in the global trade body interferes with his plan to impose penalties on companies that move American production offshore. Early actions taken by President-elect such as the appointment of so-called trade hawks to key trade positions suggest the aggressive stance taken in the campaign will likely carry over to his new Administration.